2023
DOI: 10.1111/acel.14071
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the role of immune cell composition in epigenetic age acceleration: Insights from cell‐type deconvolution applied to human blood epigenetic clocks

Ze Zhang,
Samuel R. Reynolds,
Hannah G. Stolrow
et al.

Abstract: Aging is a significant risk factor for various human disorders, and DNA methylation clocks have emerged as powerful tools for estimating biological age and predicting health‐related outcomes. Methylation data from blood DNA has been a focus of more recently developed DNA methylation clocks. However, the impact of immune cell composition on epigenetic age acceleration (EAA) remains unclear as only some clocks incorporate partial cell type composition information when analyzing EAA. We investigated associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 93 publications
3
6
0
Order By: Relevance
“…To put the 50-years-difference into perspective, the BA value difference is approximately 60 years between a 20- and 80-years-old person, but the cell type-specific difference is a few years between two persons with the same calendar age. Thus, in line with Zhang et al (2023) 24 , we conclude that calendar age and blood cell composition together explain the great majority of variation in BA values. As an exception among the BA indicators, the DunedinPACE values can have up to four-fold differences between the cell types, but the differences appear not to persist across human life course across all cell types studied here.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…To put the 50-years-difference into perspective, the BA value difference is approximately 60 years between a 20- and 80-years-old person, but the cell type-specific difference is a few years between two persons with the same calendar age. Thus, in line with Zhang et al (2023) 24 , we conclude that calendar age and blood cell composition together explain the great majority of variation in BA values. As an exception among the BA indicators, the DunedinPACE values can have up to four-fold differences between the cell types, but the differences appear not to persist across human life course across all cell types studied here.…”
Section: Discussionsupporting
confidence: 92%
“…In Kananen et al (2016), Horvath values were higher with a higher FACS-analysis-based proportions of CD4+CD28-T cells as compared to CD4+CD28+ T cells when assessed from cells originating from individuals with the same calendar age. The other previous studies have reported up to twenty-years difference in Horvath values between different cell subtypes 23,24,48 .…”
Section: Figure 4 Graphical Summary Of Typical Blood Cell Subtype Sep...mentioning
confidence: 80%
See 3 more Smart Citations